Hubungan Kekuatan Otot Tungkai Bawah dan Kinesiophobia dengan Stabilitas Fungsional dan Fungsi Lutut pada Pasien Rekonstruksi Anterior Cruciate Ligament: Tinjauan Literatur - Gede Wahyu Pratama Wijaya; I Putu Gde Surya Adhitya; Anak Agung Gede Angga Puspa Negara (PT. Kesehatan Gerak Fungsi Tubuh, 2023)
Background: One of the most prevalent knee injuries among athletes is a torn anterior cruciate ligament (ACL). ACL injuries may lead to various unpleasant symptoms, including joint instability, muscular atrophy, and soreness. ACL reconstruction is usually recommended to restore peace and function to the knee joint. After ACL reconstruction, knee muscle strength can remain compromised, leading to deficits in stability and functional limitations. ACL reconstruction also has psychological consequences, such as fear of moving due to injury or kinesiophobia. Purpose: To determine the relationship between lower leg muscle strength and kinesiophobia with functional stability and knee function in patients with ACL reconstruction. Method: The research method used is a literature review using data from scientific articles in scientific journal databases related to muscle strength, kinesiophobia, functional stability, and knee function after ACL reconstruction. The literature search used the keywords